Determinación de material partículado pm₁₀ y pm₂‚₅ en canteras de Puzolana del barrio san Felipe, parroquia Eloy Alfaro, cantón Latacunga, provincia de Cotopaxi, periodo 2019-2020. - Benavides Castro, Daniela Estefania (2020)
The pollution represent an important environmental risk, the contaminants with the greatest impact is the particle material exceeding the protection thresholds, originated in a natural and anthropogenic way, the emission source depends of the size, this research project was carried out in San Felipe´s neighborhood with the objective of determining the concentration of PM₁₀ and PM₂‚₅ particulate material in pozzolan roads, generated by quarrying, transportation of raw material, block making, delivery of the finished product and vehicular circulation. Four objectives were proposed: Characterize the study area, Monitor the concentration of particulate material, generate a database and compare the results with the Ecuadorian Environmental Regulations, Propose prevention and mitigation measures. The monitoring of PM₁₀ and PM₂‚₅ particulate material was carried out by using the E-BAM equipment, with a sampling methodology using the Beta Attenuation principle, the suspended particles are impregnated in the filter located between the source and the detector generating a signal attenuation in the beta count, to determine the mass concentration of the particulate material in the filter.